Exploring the Role of Empathy and Ethics in Enhancing Organizational Creativity and Performance: A Systematic Review - Mafriningsianti, Evi; Nugroho, Arissetyanto; Zulkifli (GoAcademica Research & Publishing, 2025)
This study investigates the interrelationships among empathy, ethical interaction, organizational rewards, creativity, and organizational performance through a Systematic Literature Review (SLR) of peer-reviewed journal articles published between 2013 and 2023. A total of 48 relevant studies were identified and analyzed from major databases including Scopus, Web of Science, Google Scholar, and ScienceDirect. The findings indicate that empathy fosters psychological safety, encourages open idea exchange, and enhances both individual and team creativity. Ethical interaction significantly contributes to organizational trust, employee satisfaction, and improved performance. Furthermore, organizational rewards play a critical role in motivating behavior, reinforcing ethical values, and stimulating innovation when aligned with intrinsic goals. However, the existing literature remains fragmented, with limited integrative models combining all five variables, and is dominated by studies from private-sector contexts. The widespread use of cross-sectional designs also restricts understanding of long-term causal dynamics. This review identifies key enabling factors—such as transformational leadership, inclusive work culture, and trust—alongside challenges like cultural resistance, power asymmetries, and a lack of ethical role models. The study provides a conceptual foundation for future empirical research and practical insights for leaders aiming to embed empathy, ethics, and reward systems into organizational strategies to foster creativity and sustainable performance.